Quantitative studies on B‐mode ultrasound and point shear wave elastography of kidneys in nonazotemic dogs - Jena, Biswadeep; Mohindroo, Jitender; Gupta, Kuldip; Singh, Navdeep (Veterinary radiology & ultrasound, 2024)
Renal diseases in dogs can be diagnosed effectively using B‐mode ultrasound. Point shear wave elastography (pSWE) has demonstrated usefulness in diagnosing renal diseases in human medicine. However, its application in veterinary medicine is in its nascent stage. It was hypothesized that establishing pSWE reference values in nonazotemic dogs would prove valuable in differentiating renal diseases. In light of this, a single‐center, quantitative study with an objective to normalize B‐mode ultrasound parameters and pSWE values of the kidney in nonazotemic dogs was conducted. A total of 198 animals presented with clinical signs of anorexia, vomiting, weight loss, and dehydration were enrolled in the study spanning 2 years. Among them, 52 nonazotemic dogs were included as subjects for the study. B‐mode ultrasound quantitative parameters, including length (L), breadth (B), height (H), cortical thickness (RCT), and medulla thickness (RMT) of the kidneys, as well as the diameter of the aorta (Ao), were normalized. Additionally, calculated parameters such as L:Ao, B:Ao, H:Ao, RCT:Ao, and corticomedullary ratios were worked out. Point shear wave elastography values were obtained from the cranial and caudal poles of renal cortices using ElastPQ stiffness software. The pSWE values of kidneys in nonazotemic dogs were normalized. The mean ± standard error values were 1.04 ± 0.08 m/s (95% confidence interval: 0.88–1.19 m/s) and 4.18 ± 0.62 kPa (95% confidence interval: 2.93–5.42 kPa). In conclusion, B‐mode ultrasound quantitative parameters, ratios, and pSWE values were normalized in nonazotemic dogs, which may prove valuable in differentiating renal pathologies in canine patients.